(untitled) (Collection of scientific works «Modern structures of metal and wood», 2021)
In the modern construction of buildings and structures there are many constructive solutions for connecting the rafter with the column of wooden three-hinged portal frames. One of these constructive solutions is the use of knee joints executed as joint on glued-in rods. Despite the accumulated experience in the construction of buildings using timber structures with joints on glued- in rods, there are still urgent tasks to improve the technology of their manufacture and calculation models. The purpose of this work was to conduct experimental and theoretical studies of the knee joint executed as joint on glued-in rods to determine the stress-strain state of the timber in the connection region. To develop of proposals for improving knee joint executed as joint on glued-in rods. The study of the stress-strain state of the knee joint was carried out by solving a plane problem of the theory of elasticity using a software package based on the finite element method. In the software package used, procedures are implemented to take into account the anisotropy of the mechanical properties of wood, the violation of contact between the surfaces of the elements connected in the knee joint. Experimental studies were carried out by the method of static loading of a prototype of a knee joint made in full size, which in its geometric parameters and material properties corresponded to the CE model. As a result of the conducted studies, it was found that in the stretched zone of the knee joint, the glued rods of the rafter and the column are characterized by a significant uneven distribution of forces, in addition, the rods are subjected to compression, tension and bending. The most loaded are the rods located at the maximum distance from the joint of the rafter and the column. The distribution of forces in the rods of the compressed zone is close to uniform. The stress distribution along the length of the inclined rods of the embedded parts is characterized by a large unevenness. Based on the analysis of the stress-strain state of the knee joint of the frame, a new design solution is proposed in terms of the number of glued-in rods and their spacing.